Peningkatan Kompetensi Guru dalam Penggunaan Teknologi Informasi Melalui Kegiatan Workshop Penggunaan Teknologi Informasi dalam Pembelajaran di SMA Negeri 12 Samarinda - Sulistiani, Ida (PT Literasi Nusantara Publisher, 2023)
Technological developments in the current era of globalization are very rapid. For this reason, the community is required to make a change in each of its activities. Teachers are expected to be able to follow these changes to improve the quality of teaching and learning activities. This research aims to find alternative solutions to problems to increase teacher competence in utilizing information technology through the Workshop on Making Technology-Based Teaching Media to increase students' learning motivation. This school action research was conducted at SMA Negeri 12 Samarinda with nineteen teachers at SMA Negeri 12 Samarinda. The aspects that are measured in the observation are the enthusiasm of the participants in following the lesson, the interaction of the students with the teacher in the teaching and learning process, the interactions with students and students in group work, and the activities of students in group discussions This is activity concluded that using information technology in teaching is very important and provides many benefits for teachers and students. These benefits are efficiency, accessibility, interactivity, personalization, and continuous learning.